2009
DOI: 10.1111/j.1349-7006.2009.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Pin1 induction in epithelial–mesenchymal transition of tamoxifen‐resistant breast cancer cells

Abstract: Acquisition of resistance to tamoxifen is a critical therapeutic problem in breast cancer patients. Epithelial-mesenchymal transition (EMT), where cells undergo a developmental switch from a polarized epithelial phenotype to a highly motile mesenchymal phenotype, is associated with invasion and motility of cancer cells. Here, we found that tamoxifen-resistant (TAMR)-MCF-7 cells had undergone EMT, as evidenced by mesenchymal-like cell shape, downregulation of basal E-cadherin expression, and overexpression of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 54 publications
5
80
0
Order By: Relevance
“…These results were confirmed in other types of tumors like gemcitabine-resistant pancreatic cancer cells, oxaliplatin-resistant colorectal cancer cells, lapatinib-resistant breast cancer [120]. In addition, tamoxifen-resistant breast cancer cells undergone EMT with altered -catenin phosphorylation [128]. It has been indicated that mesenchymal-like cancers might be more sensitive to DNA damaging agents such as doxorubicin, whereas epithelial-like cancers are more sensitive to targeted therapies, such as EGFR and HER2 antagonists [129].That may be the reason why mesenchymal-like, basal breast cancers are initially more sensitive to chemotherapy than epithelial-like luminal breast cancers [130].…”
Section: Emt and Mdrsupporting
confidence: 71%
“…These results were confirmed in other types of tumors like gemcitabine-resistant pancreatic cancer cells, oxaliplatin-resistant colorectal cancer cells, lapatinib-resistant breast cancer [120]. In addition, tamoxifen-resistant breast cancer cells undergone EMT with altered -catenin phosphorylation [128]. It has been indicated that mesenchymal-like cancers might be more sensitive to DNA damaging agents such as doxorubicin, whereas epithelial-like cancers are more sensitive to targeted therapies, such as EGFR and HER2 antagonists [129].That may be the reason why mesenchymal-like, basal breast cancers are initially more sensitive to chemotherapy than epithelial-like luminal breast cancers [130].…”
Section: Emt and Mdrsupporting
confidence: 71%
“…We showed that the Pin1 protein level was consistently increased in TAMR-MCF-7 cells compared to control MCF-7 cells (Kim et al, 2009a;2009b) (Fig. 1A).…”
Section: Transcriptional Activation Of the Pin1 Gene In Tamr-mcf-7 Cellsmentioning
confidence: 84%
“…Unfortunately, resistance to hormonal therapy is a major clinical problem -most cancer cells can utilize alternative mechanisms for growth and survival after initiation of first-line endocrine therapy (Ali et al, 2002). A series of our studies revealed that both VEGF-mediated angiogenesis and snail-dependent epithelial mesenchymal transitions were stimulated in TAMresistant breast cancer cells, and Pin1 overexpression in this cell type is a critical event for both processes (Kim et al, 2008;2009a;2009b). In the present study, we demonstrated that Pin1 overexpression in TAMR-MCF-7 cells was dependent on transcriptional activation of the Pin1 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pin1 siRNA treatment resulted in decreased Snail transcription and the expression of EMT markers. It was inferred that pin1 might take part in EMT by affecting pTEN expression and the subsequent pI3-kinase-Akt-dependent GSK-3β inactivation (62). Axl is a transmembrane tyrosine kinase receptor, activated by either its ligand-growth arrest specific 6 or extracellular domain-mediated dimerization or cross-talk with human EgFR2.…”
Section: Certain Genes Involved In Emt and Drug Resistance In Breast mentioning
confidence: 99%